NARRATIVE FOR TERRORISM AND TRANSNATIONALISM ISISTHEOLOGY THROUGH THE DOCTRINE OF RELIGION - Zuhdi, Muhammad Luthfi; Hayatullah, Imam Khomaeni (Journal of Terrorism Studies, 2020)
Acts of terrorism seem to never run out of Indonesia, from independence to the present day. Including the ideals of the establishment of an "Islamic State" that gave rise to a new wave of terrorism. The JAD group affiliated with ISIS clearly states that the Indonesian republic is Thogut, so it is haram to be obedient to it, and they commit an act of terror some time ago. ISIS cleverly uses religious propositions to recruit new members. The verses of the Qur'an and the Sunnah of the Prophet became his legitimacy. The concept of Hijra, Necrophilia and millenarism became the main doctrine of the ISIS. ISIS uses this narrative to facilitate and call for action in Indonesia. Suicide bombing, police station attack carried out by sympathizers, either JAD members or lone wolf. ISIS also utilizes social media well, this facilitates the idea of necrophilia, millenarism of ISIS is practiced by its sympathizers. Through qualitative and text analysis and the idea approach, necrophilia from Erich Fromm and millenalism from Norman Cohn, and other narrative this research is intended to make counter narrative of ISIS. so that the emergence is the concept of biophilia and optimism against the times and build a better future.